Design and performance evaluation of a variable-rate orchard sprayer based on a laser-scanning sensor - Cai, Jichen; Wang, Xiu; Gao, Yuanyuan; Yang, Shuo; Zhao, Chunjiang (International Journal of Agricultural and Biological Engineering, 2019)
To improve the precision spraying strategy and reduce excessive pesticide application in orchards, an air-assisted sprayer integrated with a laser-scanning system was developed to realize the toward-target variable-rate spraying. In the spray control system, a method of calculating canopy gridding volumes was designed to ensure the canopy was divided into a uniform grid size, a variable-rate spray model was used in the flow rate decision software to control the spray output according to the canopy gridding volumes and travel speed, and a method of saving and accessing spray data was used to control the spray delay. The effects of different grid sizes and travel speeds on the spray performance were evaluated by quantifying spray coverage uniformity inside tree canopies. The results showed that spray coverage uniformity declined with increasing grid width from 0.14 to 0.28 m although the mean spray coverage on each target location showed no significant differences. Additionally, there were no significant variations in mean spray coverage at speeds of 1.0, 1.2 and 1.4 m/s for a tested tree of 1.6 m width and at any experimental speeds for a tested tree of 1.3 m width, which indicated that the variable-rate sprayer could provide good spray coverage uniformity under various travel speeds with a canopy size limitation. Compared with the same sprayer without the variable-rate spray function, the intelligent sprayer prototype realized effective toward-target spraying and avoided overspraying while providing sufficient spray coverage.Keywords: laser-scanning sensor, variable-rate spray, orchard, precision sprayer, pesticide application efficiencyDOI: 10.25165/j.ijabe.20191206.4174Citation: Cai J C, Wang X, Gao Y Y, Yang S, Zhao C J. Design and performance evaluation of a variable-rate orchard sprayer based on a laser-scanning sensor. Int J Agric & Biol Eng, 2019; 12(6): 51–57.